Newnes guide to digital TV - Brice, Richard (Oxford ; Boston : Newnes, 2003)
The second edition has been updated with all the key developments of the past three years, and includes new and expanded sections on digital video interfaces, DSP, DVD, video servers, automation systems, HDTV, 8-VSB modulation and the ATSC system. Richard Brice has worked as a senior design engineer in several of Europe's top broadcast equipment companies and has his own music production company. * A uniquely concise and readable guide to the technology of digital television * New edition includes more information on HDTV (high definition) and ATSC (Advanced Television Systems Committe) - the body that drew up the standards for Digital Television in the U.S. * Written by an engineer for engineers, technicians and technical staff.
Introduction -- Foundations of television -- Digital video and audio coding -- Digital signal processing -- Video data compression -- Audio data compression -- Digital audio production -- Digital video production -- The MPEG multiplex -- Broadcasting digital video -- Consumer digital technology -- The future.
Includes bibliographical references and index.
Keywords: Digital television; Digital video; Electronic books